2021
DOI: 10.1007/s11606-021-06835-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Navigating Pregnancy and Parenthood for Physician Parents: a Framework Analysis of Qualitative Data

Abstract: BACKGROUND: Some gender-based disparities in medicine may relate to pregnancy and parenthood. An understanding of the challenges faced by pregnant physicians and physician parents is needed to design policies and interventions to reduce these disparities. OBJECTIVE: Our objective was to characterize workrelated barriers related to pregnancy and parenthood described by physicians. DESIGN: We performed framework analysis of qualitative data collected through individual, semi-structured interviews between May and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Maternal discrimination was an important subset of harassment and discrimination identified in this study and others. 20 , 21 , 22 Participants in our study selected their subspecialities and location of training to accommodate working as a parent, due to explicit warnings from other specialists and an implied understanding that some disciplines were more “family-friendly” than others. Participants also described derogatory comments about how pregnancy and parenthood impacted the workload of colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal discrimination was an important subset of harassment and discrimination identified in this study and others. 20 , 21 , 22 Participants in our study selected their subspecialities and location of training to accommodate working as a parent, due to explicit warnings from other specialists and an implied understanding that some disciplines were more “family-friendly” than others. Participants also described derogatory comments about how pregnancy and parenthood impacted the workload of colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Medical leaders can advocate for systems-level changes to support pregnancy and parenthood in cardiology, including call-schedule flexibility, identifying lactation spaces, and advocating for onsite childcare. 20 , 23 In addition, medical leaders must act in the moment to address maternal discrimination, including casual remarks that denigrate the work ethic or potential of mothers, or refer to parenthood as an inconvenience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from the San Francisco Bay area from 2016 to 2017 revealed that, compared to white women, Asian, Hispanic, and non-Hispanic Black women received 0.9, 2, and 3.6 less weeks of paid maternity leave (Goodman et al, 2021 ). Paid parental leave within healthcare, especially among physicians, continues to also be extremely challenging (Freeman et al, 2021 ). This is especially important because paid parental leave can be protective against peripartum health complications, which are higher in minorities (Montoya-Williams et al, 2020 ; Van Niel et al, 2020 ).…”
Section: Amc’s Financial Commitment To Recruiting and Retaining Minor...mentioning
confidence: 99%
“…Due to this lack of systems-level guidance, the experiences of women physicians are variable both between and within organisations. 7 Pregnant physicians may experience a greater prevalence of complications than other groups, 8 including more frequent preterm labour [9][10][11] and pregnancy loss, 12 though the literature is conflicting. 13 14 Further, the relationship between modifiable aspects of physician work that contribute to these worse outcomes is not well described.…”
Section: Introductionmentioning
confidence: 99%